1989
DOI: 10.1111/j.1447-0756.1989.tb00171.x
|View full text |Cite
|
Sign up to set email alerts
|

Leukoencephalopathy Following Treatment with Carmofur: A Case Report and Review of the Japanese Literature

Abstract: A 53‐year‐old woman was treated with 5 courses of CAP treatment following operation for FIGO Stage Ia cancer of the ovary in September 1986. And in April 1987, she started an oral adjuvant chemotherapy with 400 mg/day of carmofur. In early June, she developed vertigo and dysarthia and was hospitalized. A CT scan showed low‐density areas adjacent to both lateral ventricles, and an EEG revealed abnormally slow waves. She improved gradually after carmofur was discontinued and left the hospital in October 1987. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Carmofur 24 has been used to treat colorectal cancer in China, Japan, and Finland for many years . However, the agent has been shown to induce delayed leukoencephalopathy, characterized by progressive damage to white matter in the brain with stroke-like symptoms. There are currently no open clinical trials for this agent. A trial treating patients with stage II hepatocellular carcinoma was suspended prematurely, because 56% of the treated patients had unacceptable side effects and offered no survival advantage for certain cancers in stage 1 and 2 of the disease .…”
Section: Pyrimidine Analogsmentioning
confidence: 99%
“…Carmofur 24 has been used to treat colorectal cancer in China, Japan, and Finland for many years . However, the agent has been shown to induce delayed leukoencephalopathy, characterized by progressive damage to white matter in the brain with stroke-like symptoms. There are currently no open clinical trials for this agent. A trial treating patients with stage II hepatocellular carcinoma was suspended prematurely, because 56% of the treated patients had unacceptable side effects and offered no survival advantage for certain cancers in stage 1 and 2 of the disease .…”
Section: Pyrimidine Analogsmentioning
confidence: 99%
“…However, treatment with carmofur did not extend the lifespan of twitcher mice ( 63 ); rather, it was only effective in twitcher mice that were also heterozygous for acid ceramidase deficiency ( 5 ). Unfortunately, human cancer patients treated with carmofur can have drug related side effects that include leukoencephalopathy, liver dysfunction, neuropathy, skin rash, and diarrhea ( 64 – 67 ). The potential side effect of leukoencephalopathy is worrisome since the pathological changes ongoing in Krabbe disease may make the patient more susceptible to this adverse effect.…”
Section: Substrate Reduction Therapy Targeting Acid Ceramidasementioning
confidence: 99%
“…The cause of pollakiuria was also identified as associated with stimulation on micturition reflex center in brain by CPEFU (Koyama, 1981). Later studies reported leukoencephalopathy with stroke like symptoms which gradually damaged the white matter of the brain (Baehring & Fulbright, 2008; Fujikawa et al, 2001; Kuzuhara et al, 1987; Matsumoto et al, 1995; Yamada et al, 1989). Another case study presented carmofur induced organic mental disorder during the prognostic phase after the inception of leukoencephalopathy (Suzuki et al, 1990).…”
Section: Side Effect(s) With Carmofur Therapymentioning
confidence: 99%